2002
DOI: 10.17221/5821-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Lactic acid bacteria, probiotics and immune system

Abstract: Mucous membranes of the body are in direct contact with the outside environment and they are colonised by a large number of different bacteria. Through mucous membranes, the organism is in permanent con-tact with different antigens. Mucous surfaces are protected by many defence mechanisms that ensure a permanent and effective protection. They include the production of secretory IgA, the production of mucus, cytoprotective peptides, defensins etc. Indigenous microflora markedly affects the structure of the host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 81 publications
0
42
0
5
Order By: Relevance
“…This correlates with the earlier studies of Mourao et al (2006) who reported that decreasing the number of pathogenic bacteria in the gut may improve the capacity epithelial cells to build villi and thus enhance intestinal morphology, influence intestinal morphology, either by neuroendocrine factors or by the products that these microorganisms secrete (Barbara et al 2005). Lactic acid bacteria influence the distribution and the numbers of lymphoid cells in lymphatic tissues associated with the gut, ensure the balance in the composition of the gut microflora, and through their activity are able to maintain the integrity of the gut mucous membrane (Herich and Levkut 2002). Crypt depth did not significantly differ among the groups; however, Bifidiobacteium spp.…”
Section: Discussionmentioning
confidence: 99%
“…This correlates with the earlier studies of Mourao et al (2006) who reported that decreasing the number of pathogenic bacteria in the gut may improve the capacity epithelial cells to build villi and thus enhance intestinal morphology, influence intestinal morphology, either by neuroendocrine factors or by the products that these microorganisms secrete (Barbara et al 2005). Lactic acid bacteria influence the distribution and the numbers of lymphoid cells in lymphatic tissues associated with the gut, ensure the balance in the composition of the gut microflora, and through their activity are able to maintain the integrity of the gut mucous membrane (Herich and Levkut 2002). Crypt depth did not significantly differ among the groups; however, Bifidiobacteium spp.…”
Section: Discussionmentioning
confidence: 99%
“…Quant à la levure, les effets stimulants ou régulateurs des probiotiques, c'est-à-dire des microorganismes vivants sur la réponse immunitaire, ont fait l'objet de plusieurs travaux de recherche (Ashraf et Shah, 2014 ;Coates et McColl, 2001). Ces effets ont été observés sur les cellules immunitaires impliquées dans les mécanismes de défense non spécifique par activation des macrophages (Herich et Levkut, 2002) et sur le système immunitaire sécrétoire notamment des immunoglobulines A sécrétoires dans la lumière intestinale (Isolauri et al, 2001). En effet, des études aussi bien anciennes que récentes ont montré l'implication des extraits de paroi de levure S. cerevisiae, tel que le Zymosan, dans le système immunitaire (Miura et al, 1999).…”
Section: ■ Resultatsunclassified
“…En effet, des études aussi bien anciennes que récentes ont montré l'implication des extraits de paroi de levure S. cerevisiae, tel que le Zymosan, dans le système immunitaire (Miura et al, 1999). D'autres travaux ont signalé que ce sont en fait les β-glucanes de la paroi qui sont responsables de la stimulation du système immunitaire (Lee et al, 2001), probablement à travers leurs effets sur l'activation des macrophages (Herich et Levkut, 2002 ;Sarazin et al, 2010). En outre, les mannanes de la paroi de levure seraient capables de stimuler le système immunitaire chez le rat (Ataoglu et al, 2000).…”
Section: ■ Resultatsunclassified
See 1 more Smart Citation
“…해하여 장내 유해 세균에 항균작용을 하는 것으로 알려져 있 다 [6,7]. 최근에는 김치의 발효에 관여하는 젖산세균이 감기 에 대한 저항력과 조류인플루엔자의 조절에도 관여하는 것 으로 보고되고 있어 많은 관심이 집중되고 있다 [8,9].…”
unclassified